Capacity Building in e-Health and Health Informatics: A Review of the Global Vision and Informatics Educational Initiatives of the American Medical Informatics Association - Detmer, D. E. (Yearbook of Medical Informatics, 2010)
Substantial global and national commitment will be required for current healthcare systems and health professional practices to become learning care systems utilizing information and communications technology (ICT) empowered by informatics. To engage this multifaceted challenge, a vision is required that shifts the emphasis from silos of activities toward integrated systems. Successful systems will include a set of essential elements, e.g., a sufficient ICT infrastructure, evolving health care processes based on evidence and harmonized to local cultures, a fresh view toward educational preparation, sound and sustained policy support, and ongoing applied research and development.Increasingly, leaders are aware that ICT empowered by informatics must be an integral part of their national and regional visions. This paper sketches out the elements of what is needed in terms of objectives and some steps toward achieving them. It summarizes some of the progress that has been made to date by the American and International Medical Informatics Associations working separately as well as collaborating to conceptualize informatics capacity building in order to bring this vision to reality in low resource nations in particular.
Keywords: e-Health; biomedical informatics; health informatics; education; capacity building; complex adaptive systems; information and communications technology (ICT); applied clinical informaticians; AMIA Global Partnership Program